Traditional Medicinal Plants Knowledge of Tengger Ethnic: Descriptive Study in Pasuruan, Probolinggo, and Lumajang Distric - Pribadi, Eko Teguh; Santi, Dwi Rukma (International Conference on Sustainable Health Promotion, 2018)
Tengger ethnic is a Javanese sub-tribe that is rich in mystical culture including in a local tradition of treatment, which live on the slopes of Mount Semeru and Bromo. This is a descriptive study to explore the knowledge of the Tengger ethnic community related to the use of local plants as treatment and traditional health care. The study was conducted in 2015 on the Tengger ethnic group that inhabited in 5 villages located at Probolinggo, Pasuruan, and Lumajang district. The result shows that the Tengger ethnic has knowledge related to the use of medicinal plants, but this knowledge is threatened to disappear because Tenggerese people no longer practice it in their daily lives. Medicinal plants are mostly use for labor and baby care, wound treatment, and other disorders related to fatigue and activities. Plant sections commonly uses as medicinal ingredients are leaves, followed by other sections such as tubers and rhizomes. The existence of medicinal plants is relatively easy to find around the yard, but some types of plants can only be found in forests or mountains. Further studies in exploring, inventorying, and documenting Tengger ethnic local wisdom regarding the knowledge of traditional medicinal plants must continue.